Impact of Parametrized Nonorographic Gravity Wave Drag on Stratosphere‐Troposphere Coupling in the Northern and Southern Hemispheres - Inna Polichtchouk; Theodore G. Shepherd; Nicholas J. Byrne (Geophysical Research Letters)
Abstract The impact of parametrized nonorographic gravity wave drag (NOGWD) on the stratosphere‐troposphere dynamical coupling in atmospheric models is relatively unexplored. Using the European Centre for Medium‐Range Weather Forecasts Integrated Forecast System, we find that changes in NOGWD strength have a substantial impact on the tropospheric eddy‐driven jet (EDJ) in both hemispheres, but the sense of the impact is opposite in the two hemispheres. In the Northern Hemisphere the impact occurs via changes in the amplitude and persistence of stratospheric anomalies. In the Southern Hemisphere it occurs instead via differences in the sensitivity of the EDJ to a given stratospheric anomaly, arising from changes in the seasonal cycle leading up to the polar vortex breakdown. Increasing NOGWD eliminates the springtime phase of the Southern Hemisphere tropospheric semiannual oscillation, resulting in a more equatorward annual‐mean EDJ and showing that the semiannual oscillation cannot be explained entirely from tropospheric mechanisms.